2018
DOI: 10.1111/and.13157
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of different primary treatments for prostate cancer: A critical analysis

Abstract: Limited attention has been given to the psychological impact of primary treatments in patients with prostate cancer. Aim of our analysis was to critically analyse the current evidence on the psychological impact of different primary treatments (surgery, radiotherapy and active surveillance), in patients with prostate cancer, using validated questionnaires. We searched in the MEDLINE and Cochrane library database from the literature of the past 15 years (primary fields: prostate neoplasm, AND radical prostatect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 38 publications
0
38
0
1
Order By: Relevance
“…Urinary incontinence is widely recognised as one of the most debilitating complications following prostatectomy, with significant impact of cancer survivors’ quality of life. Recent research on the psychological burden of PPI has demonstrated the extent of its detrimental effects, including increased cognitive dysfunction, anxiety and depression [ 19 , 20 ]. As a consequence, the selection of surgical treatment for PPI, and predicting the outcomes of surgery are critical metrics for prostate cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence is widely recognised as one of the most debilitating complications following prostatectomy, with significant impact of cancer survivors’ quality of life. Recent research on the psychological burden of PPI has demonstrated the extent of its detrimental effects, including increased cognitive dysfunction, anxiety and depression [ 19 , 20 ]. As a consequence, the selection of surgical treatment for PPI, and predicting the outcomes of surgery are critical metrics for prostate cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 Also, differences in mental distress and psychiatric disorders were not found between patients undergoing prostatectomy, AS and radiotherapy. 15,16 In terms of need for psychosocial support, various studies in Germany found that approximately 20% of patients with prostate cancer wish to have psychosocial support. 8,17,18 This number is low compared to cancer patients in general, of which every third patient expresses a wish for psychosocial support.…”
Section: Introductionmentioning
confidence: 99%
“…5,12 Also, differences in mental distress and psychiatric disorders were not found between patients undergoing prostatectomy, AS and radiotherapy. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Although AS is intended to avoid or delay unnecessary radical treatment, it is not without costs and concerns to patients and their physicians [6,7]. A patient's anxiety about a cancer diagnosis or preference for an aggressive approach in the absence of clinical progression could be a trigger for choosing alternative treatments [8,9]. Some patients may not be compliant with follow-up, thus exposing them to the risk of disease progression [10].…”
Section: Introductionmentioning
confidence: 99%